Pelatihan Makhrojul Huruf dan Tajwid Untuk Meningkatkan Potensi Anak Dalam Membaca Al-Qur’an Di Desa. Kasembon Kec.Kasembon Kab.Malang - M. Hanif Satria Budi; Wiwin (LP3M IAIFA Kediri, 2021)
The Qur'ān (Arabic: القرآن) is the holy book of Islam. Muslims believe that the Qur'an is the culmination and closing of God's revelation which is reserved for man, and part of the pillars of faith, which were conveyed to the Prophet Muhammad (peace be upon him), through the intercession of the Angel Gabriel. And as the first revelation received by the Prophet (peace be upon him) is as found in QS Al-'Alaq/7:1-5. In the sense of tajwid science it is explained, that the scope of tajwid is concerned with reciting hijaiyah letters and how to pronounce the letters as well as possible, whether it is read long, thick, thin, stop bright, buzzing, and so on. If the letter is pronounced as the ordinance, Then the function of tajwid as a science to improve the procedures for reading the Quran is fulfilled and saves the reader from prohibited deeds. Immediately develop or increase the development of the potential of children in improving religion, by knowing the letters of the Qur'an and being able to recite the letters of the Qur'an eloquently and correctly. So that the pronunciation of makhrojul letters is arranged and with tajwid learning that applies its laws when reading the Qur'an so as to get maximum value.